Sharp Bound of the Number of Zeros for a Liénard System with a Heteroclinic Loop - Junning Cai; Minzhi Wei; Guoping Pang (Discrete Dynamics in Nature and Society)
In the presented paper, the Abelian integral Ih of a Liénard system is investigated, with a heteroclinic loop passing through a nilpotent saddle. By using a new algebraic criterion, we try to find the least upper bound of the number of limit cycles bifurcating from periodic annulus.